Sosialisasi E-Safety Parenting Sebagai Smart Solution dalam Pendampingan Penggunaan Gadget Pada Anak - Haryani, Prita (Universitas Nusantara PGRI Kediri, 2019)
The e-safety parenting socialization activity aims to provide knowledge about patterns of childcare in the digital era in using smartphones, especially the use of the Internet. The socialization activities were attended by 38 participants fromTrayeman village, Plered, Bantul. The method used is lecture and question and answer. Socialization material is distributed in the form of material handouts. The implementation of e-safety parenting is getting a good response. The participants were enthusiastic in listening to lectures from the speakers. This can be seen from the many questions raised related to childcare patterns in the digital age in using smartphones, especially Internet usage. After participating in this socialization, the participants of the socialization have understood the potential or risks of children using the Internet, tips on using the Internet wisely and knowing the procedures and techniques for the prevention of negative content on the Internet. Socialization participants can also practice the steps of using the Secure Parental Control App on their smartphone. It is hoped that by taking part in the socialization of e-safety parenting, they will discuss the negative impacts of using gadgets and direct the use of these gadgets for positive activities.